2022
DOI: 10.3390/su14042428
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Hotel Employees’ Organizational Citizenship Behavior: The Roles of Organizational Pride and Meaningfulness of Work

Abstract: The corporate social responsibility (CSR) literature documents inconsistent results regarding the relationship between CSR and employees’ organizational citizenship behavior (OCB). Additionally, few empirical studies examine the mediating factors explaining how employees’ CSR perception affects their attitudes and behaviors. Thus, we propose an extended M-R model linking hotels’ CSR activities, employees’ perceived meaningfulness of work and organizational pride, and organizational citizenship behavior. We rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
3
18
0
1
Order By: Relevance
“…Having a strong perception of the organizations CSR activities will contribute to the experience that the organization has values that are useful and worth identifying with, and through that the employees experience a sense of belonging and meaningful co-existence. Recent studies support the positive relationship between CSR and the experience of meaningfulness at work ( Chaudhary, 2020 ; Youn and Kim, 2022 ). Accordingly, we posit the following hypothesis;…”
Section: Theory and Hypothesismentioning
confidence: 94%
“…Having a strong perception of the organizations CSR activities will contribute to the experience that the organization has values that are useful and worth identifying with, and through that the employees experience a sense of belonging and meaningful co-existence. Recent studies support the positive relationship between CSR and the experience of meaningfulness at work ( Chaudhary, 2020 ; Youn and Kim, 2022 ). Accordingly, we posit the following hypothesis;…”
Section: Theory and Hypothesismentioning
confidence: 94%
“…Moreover, although we conducted several tests to rule out common method bias, this study employed a self-report survey method. The study also did not control for potential endogeneity issues that could find a reverse effect for employees' AOC and the influence on their perception of CSR [82]. Future studies could verify the findings by using data from multiple sources (e.g., from supervisors), using data collected at different times, and also using objective data.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…The positive relationship between employees’ social responsibility and their own behavior becomes stronger when leaders motivate frontline employees to serve customers. Furthermore, when frontline employees are satisfied with their jobs, the relationship between responsibility, self-esteem, and their own behavior is strengthened [ 21 , 22 ]. Lau [ 23 ] found that teachers who perceived the principal’s trust had higher task performance and organizational citizenship behavior, and organizational self-esteem played a positive moderating role between perceived trust and organizational citizenship behavior and task performance.…”
Section: Relevant Theoretical Basismentioning
confidence: 99%